Giving Alms to Palestine: Evidence of Millennial Muslim Awareness in Kerinci - Fitri, Khatimul; Fauzi, Muhammad; Arzam, Arzam (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
Millennial Muslims in Kerinci are supposed to give alms to Palestine who are currently in need, which is not just a discourse but rather produces concrete evidence in significant acts of alms. The research aims to examine the level of awareness of giving alms to Palestine among millennial Muslims in Kerinci. The level of awareness tested is in the form of knowledge, attitudes and actions carried out by millennial Muslims. This research uses quantitative descriptive research. Research data was collected from primary data in the form of questionnaires that were distributed and answered by 100 millennial Muslims in Kerinci, using descriptive analysis as a data analysis tool. The findings of this research show that the level of awareness of giving alms to Palestine among millennial Muslims in Kerinci is very high. This is reflected in knowledge, attitudes and actions obtaining very high scores (percentages). The implications of the results of this research can be used as a basis for developing more effective strategies and policies in gathering community support to help Muslim brothers and sisters in need